2014
DOI: 10.1097/scs.0000000000000667
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular Synovial Chondromatosis With Numerous Nodules

Abstract: Synovial chondromatosis of the temporomandibular joint is an uncommon disorder with an indolent clinical course and a slow progression. We report a rare case of unilateral early synovial chondromatosis of the temporomandibular joint with numerous nodules and discuss possible etiologies for the entity of loose bodies and the evolution of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The temporomandibular joint (TMJ) is occasionally affected by chronic pathologies such as chondromatosis or OA [ 5 , 8 , 9 ]. OA can result in cortical bone erosion, flattening of joint compartments, osteophyte formation, subchondral sclerosis, and subcortical cyst formation [ 2 , 5 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The temporomandibular joint (TMJ) is occasionally affected by chronic pathologies such as chondromatosis or OA [ 5 , 8 , 9 ]. OA can result in cortical bone erosion, flattening of joint compartments, osteophyte formation, subchondral sclerosis, and subcortical cyst formation [ 2 , 5 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, not all of these reports included a histological analysis of the loose bodies or performed arthroscopic evaluation of the affected joints (Adame et al., 1998; Schellhas et al., 1989), which questions the definitive diagnosis of OC. One possible differential diagnosis for loose bodies in the human TMJ is synovial chondromatosis, which can present as multiple, small, calcified or ossified fragments in the joint (Cascone et al., 2014; Sink et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have observed that patients with depression and catastrophic pain are more likely to develop a TMD [ 7 ]. Possible aetiologies of TMD are chronic pathologies of the temporomandibular tissues, such as chondromatosis [ 8 ]. Moreover, given that it occurs in other persistent pain procedures, patients with TMDs could initiate compatibles signs and symptoms with peripheral or central sensitization [ 9 ].…”
Section: Introductionmentioning
confidence: 99%